Implementing Role Play in English for Business Class - Berlinda Mandasari (Universitas Teknokrat Indonesia, 2017)
This study is aimed at describing the implementation of role play technique in English for Business class. The participants of this study were 52 students majoring informatics system at Universitas Teknokrat Indonesia who enrolled English for business I. Data were collected through observation and interview. Then, the data were analyzed by using descriptive analysis. The result of this study shows that the implementation of role play was done successfully. Students played their role well. They could use English based on its context. More exposure toward real situated activities is suggested to help students develop their English ability.